2019
DOI: 10.1111/jphp.13095
|View full text |Cite
|
Sign up to set email alerts
|

Chlorogenic acid inhibits proliferation and induces apoptosis in A498 human kidney cancer cells via inactivating PI3K/Akt/mTOR signalling pathway

Abstract: Objectives Kidney cancer is a highly lethal cancer, of which the most common type is renal cell carcinoma (RCC). The targeted drugs used in treating RCC clinically have a lot of side effects. Therefore, it is urgent to find out effective agents with little toxic effects. Methods The antiproliferation effect of chlorogenic acid (CA) was performed using the CCK-8 assay. Then, we adopted colony formation assay, Annexin V/PI staining assay and JC-1 mitochondrial membrane potential assay to explore the mechanism of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 40 publications
1
42
0
Order By: Relevance
“…The antitumor action of coffee polyphenols has been investigated in tumor cell lines, pre-clinical, and clinical studies (Rajagopal et al, 2018). Chlorogenic acid induces apoptosis and selectively inhibits proliferation of A498 human renal cancer cells but not of HEK293 human embryonic kidney cells (Wang et al, 2019). Caffeic acid inhibits proliferation of hepatocellular carcinoma cells and SK-Mel-28 human melanoma cancer cells by inducing apoptosis (Brautigan et al, 2018), alters gene expression in SK-Mel-28 cells (Pelinson et al, 2019), and attenuates the properties of cancer stem cell-like cells by increasing DNA methylating and inducing the expression of miR-148a (Li et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The antitumor action of coffee polyphenols has been investigated in tumor cell lines, pre-clinical, and clinical studies (Rajagopal et al, 2018). Chlorogenic acid induces apoptosis and selectively inhibits proliferation of A498 human renal cancer cells but not of HEK293 human embryonic kidney cells (Wang et al, 2019). Caffeic acid inhibits proliferation of hepatocellular carcinoma cells and SK-Mel-28 human melanoma cancer cells by inducing apoptosis (Brautigan et al, 2018), alters gene expression in SK-Mel-28 cells (Pelinson et al, 2019), and attenuates the properties of cancer stem cell-like cells by increasing DNA methylating and inducing the expression of miR-148a (Li et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Figure 2 and Figure 3 show possible modulations by CGA, although individual pathways in which CGA is involved have not necessarily been reported. Figure 2 illustrates CGA’s downregulation of ROS [ 2 , 11 , 48 , 120 , 127 ], DNA damage [ 123 ], EGFR [ 127 ], Akt/phosphatidyl 3-inositol kinase (PI3K) [ 127 ], ERK1/2 [ 11 , 127 ], NF-κB [ 2 , 121 , 125 , 127 , 128 ], TNF-α [ 2 , 122 ], IL-1β [ 122 ], IL-8 [ 2 , 11 ], IL-6 [ 122 ], MMPs [ 2 , 11 ], COX-2 [ 125 , 128 ], Bcl-2 [ 10 , 129 ], mTOR [ 10 , 127 ], VEGF [ 126 ], and upregulation of AMPK [ 7 , 49 ]. Although CGA’s upregulation of CaMKK and LKB1 shown in Figure 3 has not been determined yet, Park et al [ 130 ] reported upregulation of them by neochlorogenic acid, an isomer of CGA.…”
Section: Anti-cancer Effects Of Coffeementioning
confidence: 99%
“…bladder, prostate, renal carcinoma, and breast cancer (Deka et al, 2017;Yamagata et al, 2018;Wang et al, 2019b) Gallic acid anti-proliferation AKT1, CCNA/B1/D1/D3/E, CDC25C/ 2C, CDK2/4/6, CDKN1A/1B, CHEK1/2, INK4, MAPK1/14, P18, PIK3CA, SKP2…”
Section: Phenolic Acidsmentioning
confidence: 99%